Analysis of mortality in François’ langurs (Trachypithecus francoisi) managed care in Trachypithecus francoisi rare animal breeding Center in Wuzhou, Guangxi, China: a 16-year review - Xiong, Yi; Xie, Guanping; Li, Yifeng; Mo, Yasheng; Wu, Zhengjun; Li, Youbang (Frontiers in Veterinary Science, 2024)
In managed care settings, primates are susceptible to a variety of health complications. A comprehensive understanding of the causes of mortality and their association with management practices is essential for enhancing the welfare of managed care populations such as François' langurs (Trachypithecus francoisi).However, literature addressing prevalent diseases or causes of death in such settings remains limited among François' langurs in managed care. To address this knowledge gap, we conducted an analysis of mortality causes in François' langurs (n = 97) who died of natural causes during a 16-year period (2007-2022) at the Trachypithecus francoisi Rare Animal Breeding Center in Wuzhou, Guangxi, China. Morphological diagnosis and organ system and etiological evaluations were performed. François' langurs were divided into six age-range groups, following previous studies: infant (≤ 1 year old), juvenile (1 to 2 years), sub-adult (2 to 4 years), adult (4 to 10 years), middle-aged (10 to 15 years), and geriatric (> 15 years). Results revealed that the primary causes of mortality in managed care François' langurs were pneumonia (n = 11, 12.22%), neoplasia (n = 7, 7.78%), ileus (n = 7, 7.78%), senility (n = 6, 6.67%), gastroenteritis (n = 6, 6.67%), cardiac disease (n = 5, 5.56%), hemorrhage (n = 5, 5.56%), intestinal adhesion (n = 4, 4.44%), and renal abscess (n = 4, 4.44%). The gastrointestinal system was most frequently implicated in deaths, followed by the respiratory system (n = 17, 18.89%), multisystem disease (n = 16, 17.78%), and cardiovascular system (n = 15, 16.67%). Regarding etiology, infectious or inflammatory (n = 32, 35.56%) and physiological factors (n = 17, 18.89%) were identified as the leading contributors to the high mortality rate. It is imperative for managers to recognize the distinct risk profiles associated with different age groups. Specifically, pneumonia was the principal cause of death in infant and juvenile langurs, while renal disease, neoplasia, gastroenteritis, and intestinal obstruction were the primary causes of death in adult and middle-aged François' langurs and advanced age and cardiac disease were the main causes of death in geriatric langurs.